Counting Miracles : a Novel - Sparks, Nicholas (New York : Random House, 2024)
"From the acclaimed author of The Longest Ride and The Notebook comes an emotional, powerful novel about wondering if we can change-or even make our peace with-the path we've taken. Tanner Hughes was raised by his grandparents, following in his grandfather's military footsteps to become an Army Ranger. His whole life has been spent abroad, and he is the proverbial rolling stone: happiest when off on his next adventure, zero desire to settle down. But when his grandmother passes away, her last words to him are find where you belong. She also drops a bombshell, telling him the name of the father he never knew-and where to find him. Tanner is due at his next posting soon, but his curiosity is piqued, and he sets out for Asheboro, North Carolina, to ask around. He's been in town less than twenty-four hours when he meets Kaitlyn Cooper, a doctor and single mom. They both feel an immediate connection; Tanner knows Kaitlyn has a story to tell, and he wants to hear it. To Kaitlyn, Tanner is mysterious, exciting-and possibly leaving in just a few weeks. Meanwhile, nearby, eighty-three-year-old Jasper lives alone in a cabin bordering a national forest. With only his old dog, Arlo, for company, he lives quietly, haunted by a tragic accident that took place decades before. When he hears rumors that a white deer has been spotted in the forest-a creature of legend that inspired his father and grandfather-he becomes obsessed with protecting the deer from poachers. As these characters' fates orbit closer together, none of them is expecting a miracle . . . but that may be exactly what is about to alter their futures forever"--
Keywords: North Carolina -- Fiction; Romance fiction; Novels